2021
DOI: 10.1042/bst20210343
|View full text |Cite
|
Sign up to set email alerts
|

Development of next generation nanomedicine-based approaches for the treatment of cancer: we've barely scratched the surface

Abstract: Interest in nanomedicines has grown rapidly over the past two decades, owing to the promising therapeutic applications they may provide, particularly for the treatment of cancer. Personalised medicine and ‘smart’ actively targeted nanoparticles represent an opportunity to deliver therapies directly to cancer cells and provide sustained drug release, in turn providing overall lower off-target toxicity and increased therapeutic efficacy. However, the successful translation of nanomedicines from encouraging pre-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…30,50 Furthermore, the nanoparticle formulation could be further modified through the addition of pH sensitive polymers, to further tailor the nanoformulation to react to fluctuations in pH within the tumour microenvironment, where pH sensitivity can be further investigated. 51–55…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,50 Furthermore, the nanoparticle formulation could be further modified through the addition of pH sensitive polymers, to further tailor the nanoformulation to react to fluctuations in pH within the tumour microenvironment, where pH sensitivity can be further investigated. 51–55…”
Section: Discussionmentioning
confidence: 99%
“…30,50 Furthermore, the nanoparticle formulation could be further modied through the addition of pH sensitive polymers, to further tailor the nanoformulation to react to uctuations in pH within the tumour microenvironment, where pH sensitivity can be further investigated. [51][52][53][54][55] Whilst promising, utilisation of cationic particles has proven challenging. One of the key concerns regarding the potential clinical translation of such cationic nanoparticles is their increased cellular cytotoxicity, as demonstrated by studies which have shown that cationic nanoparticles at high concentrations may induce caspase 3/7 activation and PARP cleavage ultimately leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…One approach involves the integration of targeting ligands on the surface of nanoparticles or biomaterials, enabling specific recognition and binding to target cells. Additionally, the incorporation of stimuli-responsive components, such as polymers, peptides, or small molecules, allows for triggered gene release and activation (Tracey et al, 2021). Moreover, the combination of different types of biomaterials, such as lipids, polymers, and inorganic nanoparticles, can provide synergistic effects and multifunctionality to enhance gene delivery efficiency (Chen et al, 2023).…”
Section: 2) Future Perspectives and Outlook For Bioengineered Smart N...mentioning
confidence: 99%